Study on Subitizing: Exploring Numeracy Mastery in Early Childhood - Mahfudz Reza Fahlevi (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Subitizing, the ability to rapidly and accurately recognize small quantities of objects without counting, has become a primary focus in developing numeracy understanding in early childhood. The research uses a qualitative approach with literature study techniques. The study aims to provide a comprehensive overview of the concept of subitizing, learning trajectories, and recommendations for teaching it to young children, as well as concrete examples from research involving multidisciplinary approaches. The findings indicate that current research explores various aspects of subitizing, ranging from effective teaching strategies to learning trajectories appropriate for children’s developmental stages. Effective subitizing instruction includes the use of relevant number concepts in everyday interactions, practicing naming small collections of objects with numbers, and repeated experiences in recognizing and naming groups of objects. Subitizing learning trajectories encompass developmental processes and the creation of task-supportive environments, ranging from unconscious number understanding to the ability to recognize quantities up to 10 objects. Various research outcomes also highlight the application of subitizing in technology development, such as subitizing games to enhance children’s mathematical abilities and assistive software for children with dyscalculia. Studies in psychology and health fields reveal the complexity of the relationship between subitizing and cognitive functions, such as in children with specific conditions like Cerebral Palsy or brain injuries. With a multidisciplinary approach, current research continues to expand understanding of the benefits of subitizing and its implications in various contexts, from education to health, aiming to enhance children’s learning and well-being holistically.